Phenotypic and functional characterization of human memory T cell responses to Burkholderia pseudomallei. - Patcharaporn Tippayawat; Wipawee Saenwongsa; Jirawan Mahawantung; Duangchan Suwannasaen; Ploenchan Chetchotisakd; Direk Limmathurotsakul; Sharon J Peacock; Philip L Felgner; Helen S Atkins; Richard W Titball; Gregory J Bancroft; Ganjana Lertmemongkolchai (Public Library of Science (PLoS), 2009)
Infection with the Gram-negative bacterium Burkholderia pseudomallei is an important cause of community-acquired lethal sepsis in endemic regions in southeast Asia and northern Australia and is increasingly reported in other tropical areas. In animal models, production of interferon-gamma (IFN-gamma) is critical for resistance, but in humans the characteristics of IFN-gamma production and the bacterial antigens that are recognized by the cell-mediated immune response have not been defined.Peripheral blood from 133 healthy individuals who lived in the endemic area and had no history of melioidosis, 60 patients who had recovered from melioidosis, and 31 other patient control subjects were stimulated by whole bacteria or purified bacterial proteins in vitro, and IFN-gamma responses were analyzed by ELISPOT and flow cytometry.B. pseudomallei was a potent activator of human peripheral blood NK cells for innate production of IFN-gamma. In addition, healthy individuals with serological evidence of exposure to B. pseudomallei and patients recovered from active melioidosis developed CD4(+) (and CD8(+)) T cells that recognized whole bacteria and purified proteins LolC, OppA, and PotF, members of the B. pseudomallei ABC transporter family. This response was primarily mediated by terminally differentiated T cells of the effector-memory (T(EMRA)) phenotype and correlated with the titer of anti-B. pseudomallei antibodies in the serum.Individuals living in a melioidosis-endemic region show clear evidence of T cell priming for the ability to make IFN-gamma that correlates with their serological status. The ability to detect T cell responses to defined B. pseudomallei proteins in large numbers of individuals now provides the opportunity to screen candidate antigens for inclusion in protein or polysaccharide-conjugate subunit vaccines against this important but neglected disease.